Short‐duration treatment with the novel non‐nucleoside inhibitor CDI‐31244 plus sofosbuvir/velpatasvir for chronic hepatitis C: An open‐label study. Issue 6 (22nd November 2020) - Chua, Joel V.; Ntem‐Mensah, Afua; Abutaleb, Ameer; Husson, Jennifer; Mutumbi, Lydiah; Lam, Ka Wing; Ghosh, Alip; Romani, Sara; Poonia, Bhawna; Lee, Sam; Luz Pascual, M.; Frumkin, Lyn R.; et al.
Abstract: Combination regimens of direct‐acting antiviral agents (DAAs) for chronic genotype 1 hepatitis C virus (HCV) infection given for 8 or 12 weeks have high cure rates. Shortened treatment durations that maintain high cure rates may lessen treatment barriers related to affordability and drug adherence. We enrolled 12 treatment‐naïve adults with chronic genotype 1 HCV infection without cirrhosis in a single‐center, open‐label trial to receive 2 weeks of the highly potent and selective non‐nucleoside inhibitor (NNI) CDI‐31244 concurrent with 6 weeks of sofosbuvir/velpatasvir. The main efficacy endpoints were sustained virologic response at 12 (SVR12) and 24 (SVR24) weeks after treatment completion. In all patients, plasma HCV RNA levels rapidly decreased during the first 2 days of treatment and were below the lower limit of quantification by the end of the 6‐week treatment period. Eight of 12 (67%) patients achieved both SVR12 and SVR24. Four patients had virological relapse at Week 10, 4 weeks after end of treatment. The most common adverse event was headache, occurring in five (42%) patients. Pharmacokinetic analysis showed no relevant drug interactions between CDI‐31244, sofosbuvir, and velpatasvir. In this pilot study of short‐duration combination therapy involving a novel NNI with a fixed‐combination DAA, 8 of 12 treatment‐naïve patients with chronic genotype 1 HCV infection without cirrhosis achieved virologic cure. Future trials might evaluate whether extending the NNI duration beyond 2 weeks with combination DAAs results in higher cure rates comparable with currently approved longer duration therapy.